(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study investigated biochemical parameters in osteoporosis mouse model induced by prolonged glucocorticoid administration. Materials and methods: Mice were orally administered prednisone at doses of 5, 10, and 20 mg/kg/day continuously for 6 and 8 weeks. Biochemical parameters, including bone weight, ash weight, bone phosphorus and calcium content were evaluated. The model’s responsiveness (optimal dose/duration) to the anti-osteoporosis drug alendronate (5 mg/kg) was also assessed at 4 weeks post-prednisone treatment. Results: Prednisone administration significantly reduced bone weight, ash weight, bone phosphorus and calcium content, with the most pronounced effects observed at the 20 mg/kg dose over 8 weeks. Alendronate treatment at dose 5mg/kg effectively increased these parameters, restoring bone health indicators. Conclusion: The mouse model of prednisone-induced osteoporosis (20 mg/kg/day for 8 weeks) is suitable for evaluating the anti-osteoporosis efficacy of drugs and formulations in preclinical research.